Orthodontic Loop-guided Piezocision (OLP): An innovative precision aid in accelerated tooth movement. (Bangladesh Journal of Medical Science, 2022)
The Accelerated osteogenic Orthodontics (AOO) is an emerging contemporary approach for rapid movement of teeth. The acceptable length of orthodontic treatment is contested, however the need for speeding appears to be universally agreed upon. Various surgical adjuncts have been developed to expedite orthodontic tooth movement and to retain optimal occlusal results while shortening treatment timeframes. Despite this, a variety of crucial treatment decisions and approaches may have a greater impact. The purpose of present case study is to suggest a minimally invasive novel orthodontic Loop-guided Piezocision (OLP) approach for quick movement of teeth, without reflection of the flap, with higher precision and minimum postoperative problems. This technique may aid in preventing orthodontic relapse, broaden spectrum of malocclusion correction. This may also eliminates requirement of conventional ortho-surgical procedure, and completes treatment in relatively shorter active orthodontic treatment period.Bangladesh Journal of Medical Science Vol. 21 No. 02 April’22 Page : 470-476